Pembinaan Pemuda kristen tentang Pemuda, Teknologi dan Hamil diluar Nikah - Rohi, Januar D. M.; Sesfao, Maria I.; Sole, Adriana I.S.; Dethan, Yandri D. (Devotion: Jurnal Pengabdian Masyarakat, 2024)
Youth are the backbone of a nation as well as a church, therefore as youth they should do many things in life, and be the controllers of the rapid technological advances that are currently developing. However, in reality, with the advancement of existing technology, many young people fall into promiscuity (extramarital sex) which causes pregnancy. Because young people in the era of introducing technology, are still unable to control themselves well, they actually fall into habits that are detrimental to themselves, others, and society. The purpose of this community service activity is to provide education and encouragement for young people in Siloam Humone so that they can know and understand the benefits and impacts of using technology, and be wise in using technology, so that they do not fall into promiscuity. The method of implementing PKM "guidance for young people of the Siloam Humone congregation regarding youth, sex and premarital pregnancy" is divided into the following stages: 1). The implementation of community service is preceded by initial observation with the pastor and the Humone community online, 2). Implementation of community service activities for young people in Siloam Humone. The importance of implementing this activity is to provide education so that we can act wisely in the technological era so that we do not fall into free association, but must hold on to the Christian faith, so that we are not easily influenced by technological advances and bad associations.